Friday
March 24, 2017

Post a New Question

Posted by on Thursday, February 21, 2008 at 2:02pm.

Simplify: (4m/5n^2)-(n/2m)

A)(8m^2-5n^3)/10n^2m
B)(8m^2+5n^3)/10n^2m
C)(4m-n)/(5n^2-2m)
D)2/5n^2
I chose C

4m/5n^2 - n/2m
4m/5(n)^2 - n/2(m)
C

  • Algebra - , Thursday, February 21, 2008 at 4:47pm

    You need to find a common denominator for the two fractions you are trying to subtract. Simplifying the problem:
    A/B - C/D = (A*D-C*B)/(B*D)
    In this case,
    A=4m
    B=5n^2
    C=n
    D=2m
    So, A*D=4m*2m=8m^2
    C*B=n*5n^2=5n^3
    B*D=5n^2*2m=10n^2m
    Substituting this into the simplified equation gives:
    (8m^2-5n^3)/(10n^2m) which is answer (A)

    A clue to the correct answer is that (A) and (B) are only a little different, so it's probably one of them!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question